Follow-up care over 12 months of patients with prostate cancer in Spain: A multicenter prospective cohort study. Issue 47 (24th November 2021) - Bonfill, Xavier; Martinez-Zapata, María José; Vernooij, Robin WM; Sánchez, María José; Morales-Suárez-Varela, María; Emparanza, José Ignacio; Ferrer, Montse; Pijoan, José Ignacio; Palou, Joan; Madrid, Eva; Abraira, Víctor; Zamora, Javier
Abstract : Abstract: The therapeutic approach is crucial to prostate cancer prognosis. We describe treatments and outcomes for a Spanish cohort of patients with prostate cancer during the first 12 months after diagnosis and identify the factors that influenced the treatment they received. This multicenter prospective cohort study included patients with prostate cancer followed up for 12 months after diagnosis. Treatment was stratified by factors such as hospital, age group (<70 and ≥70 years), and D'Amico cancer risk classification. The outcomes were Eastern Cooperative Oncology Group (ECOG) performance status, adverse events (AEs), and mortality. The patient characteristics associated with the different treatment modalities were analyzed using multivariate logistic regression. We included 470 men from 7 Spanish tertiary hospitals (mean (standard deviation) age 67.8 (7.6) years), 373 (79.4%) of which received treatment (alone or in combination) as follows: surgery (n = 163; 34.7%); radiotherapy (RT) (n = 149; 31.7%); and hormone therapy (HT) (n = 142; 30.2%). The remaining patients (n = 97) were allocated to no treatment, that is, watchful waiting (14.0%) or active surveillance (5.7%). HT was the most frequently administered treatment during follow-up and RT plus HT was the most common therapeutic combination. Surgery was more frequent in patients aged <70, with lower histologic tumor grades, Gleason scores <7, and lower prostate-specific antigen levels; while RT was more frequent in patients aged ≥70 with histologic tumor grade 4, and higher ECOG scores. HT was more frequent in patients aged ≥70, with histologic tumor grades 3 to 4, Gleason score ≥8, ECOG ≥1, and higher prostate-specific antigen levels. The number of fully active patients (ECOG score 0) decreased significantly during follow-up, from 75.3% at diagnosis to 65.1% at 12 months ( P  < .001); 230 (48.9%) patients had at least 1 AE, and 12 (2.6%) patients died. Surgery or RT were the main curative options. A fifth of the patients received no treatment. Palliative HT was more frequently administered to older patients with higher tumor grades and higher Gleason scores. Close to half of the patients experienced an AE related to their treatment.